Pathways out of poverty during an economic crisis: an empirical assessment of rural Indonesia - Neil McCulloch; Julian Weisbrod; C. Peter Timmer (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2007)
Most poor people in developing countries still live in rural areas and are primarily engaged in low productivity farming activities. Thus pathways out of poverty are likely to be strongly connected to productivity increases in the rural economy, whether they are realised in farming, rural non-farm enterprises or via rural-urban migration. We use cross-sectional data from the Central Statistical Board (BPS) for 1993 and 2002, as well as a panel data set from the Indonesia Family Life Survey (IFLS) for 1993 and 2000, to show which pathways out of poverty were most successful over this period. Our findings suggest that increased engagement of farmers in rural non-farm enterprises is an important route out of rural poverty, but that most of the rural agricultural poor that exit poverty still do so while remaining rural and agricultural. Thus changes in agricultural prices, wages and productivity still play a critical role in moving people out of poverty.
Keywords: O12; O13; O18; O53; R11; 330; poverty dynamics; non-farm sector; micro-growth regression; Ländliche Armut; Ländliche Wirtschaft; Landwirtschaft; Agrareinkommen; Indonesien